Sugarcane PeelPro - Syed Abdul Hamid, Syed Luqmanulhakim; Aszele, Afif Haziq; Kamisan, Muhammad Fuad Hasif; Abdullah, Nurmina (Multidisciplinary Applied Research and Innovation, 2026)
Sugarcane is a vital agricultural commodity widely used for sugar production and popular consumption, particularly in Southeast Asia where sugarcane juice is a culturally significant beverage. Traditional manual peeling of sugarcane, performed with knives, is labor-intensive, time-consuming, and poses safety risks to operators, especially small-scale vendors. This project presents the design, development, and testing of the Sugarcane Peel Pro, an automatic sugarcane peeling machine aimed at improving efficiency, safety, and sustainability for local vendors. The machine features a stainless-steel rotary blade powered by a 0.75 hp motor operating at 850 rpm, housed within a sturdy mild steel frame with ergonomic design elements such as a hand-fed slot, pressure rollers, and protective blade covers. It accommodates sugarcane stalks up to 30 mm in diameter, peeling each stalk within 45 to 60 seconds with an efficiency of 85% to 90%, while consuming low power (0.5 to 0.75 kWh). Manufactured through precision machining and MIG welding processes, the machine demonstrated reliable performance during testing, with smooth operation, stable blade balance, and effective safety features. While limitations remain regarding stalk shape adaptability and reliance on electricity, the Sugarcane Peel Pro effectively reduces labor intensity, enhances user safety, and minimizes material waste, providing a practical and cost-effective solution for small-scale sugarcane juice vendors. This innovation supports social and economic sustainability by promoting safer working conditions and increased productivity within local agricultural processing industries.